Mental Health Peer Support across the Life Course: Exploring the experiences of the lived experience workforce across youth, adult, and older adult settings - Hopkins, Liza; Holt, Jan; Kuklych, Jacinta; Ferrier, Isabelle; Rozario, Jacqueline; Anson, Jessica; Stefano, Christopher (Journal of Recovery in Mental Health, 2025)
Participation of those with lived and living experience is central to recovery-oriented philosophies and practices within mental health services. Such participation provides a bridge to improving understanding between service providers and people accessing services. In doing so, lived and living experience workers often contribute to more tailored service provision and, ultimately, better outcomes for service users. Due to the siloed nature of the mental health care system, little is known about how peer work varies over the lifespan. This paper was developed and written by a combination of lived experience experts and experts by training, through a collaborative, reflexive methodology. It considers the roles of consumer and carer peer workers across the age spectrum within a single, multi-faceted, large public mental health service. We examine the shared experiences of peer workers in different parts of the service from both peer worker and non-peer worker perspectives, as well as some of the unique challenges which characterise specific cohorts. We worked collaboratively to draw out these themes, and then identify their implications for practice for other services. We also illustrate some of the potential pitfalls in implementation and development of the peer workforce within clinical settings.